Body Composition Parameters May Be Prognostic Factors in Upper Urinary Tract Urothelial Carcinoma Treated by Radical Nephroureterectomy - Pan, Yulong; Chen, Zeyu; Yang, Lanqing; Wang, Xingyuan; Yi, Zeng; Zhou, Liang; Chen, Yongjiang; Yang, Lu; Zhuo, Hui; Bao, Yige; Wei, Qiang (Frontiers in Oncology, 2021)
Objective： This study assessed the association between body composition and prognosis of patients with upper urinary tract urothelial carcinoma (UTUC) patients treated by radical nephroureterectomy. Methods: We retrospectively collected baseline data on age, sex, body mass index (BMI), hypertension, diabetes, and tumor-related factors. Computed tomography (CT) scans were performed to measure body composition parameters such as muscle attenuation (MA), total abdominal muscle area (TAMA), visceral fat area (VFA), intermuscular fat area (IMF), and lateral/posterior perirenal fat thickness (L/P PNF), visceral fat density (VD), and subcutaneous fat density (SD). Patient follow-up was conducted via telephone or in the clinic. The endpoints of follow-up were all-cause death, local progression or distant metastasis. Survival analysis was analyzed using the Kaplan-Meier method, and risk factors associated with prognosis were identified using univariate and multivariate Cox proportional hazard analyses. Results: Among the 273 UTUC patients (median age, 68 years) enrolled in our study, 102 had a BMI > 24.0, 100 suffered from diabetes, and 120 had hypertension. A large proportion of patients (189) had high grade tumors. Across all patients, 1- and 3-year rates for overall survival were 86.45% and 75.55%; local progression-free survival, 92.11% and 89.67%; and distant metastasis-free survival, 85.23% and 80.17%. Based on the Cox regression analysis, IMF and PMI significantly reduced the risk of local progression (p < 0.05), while MA, PPNF = 1 point, and TPA reduced the risk of distant metastasis (p < 0.05). Overall survival was significantly associated with MA, TAMA, and SMI (p < 0.05). Conclusion: Our findings illustrate that body composition parameters, such as MA, SMI, PMI and PPNF, can act as independent predictors of poor prognosis in UTUC patients who underwent RNU. These results can help improve stratification of patients and optimize postoperative treatment.